Evolution, Expression, and Function of Gonadal Somatic Cell-Derived Factor - Hsu, Chen-wei; Chung, Bon-chu (Frontiers in Cell and Developmental Biology, 2021)
Fish gonads develop in very diverse ways different from mammalian gonads. This diversity is contributed by species-specific factors. Gonadal somatic cell-derived factor (Gsdf) is one such factor. The gsdf gene exists mostly in teleosts and is absent in many tetrapods, probably as a result of two gene losses during evolution. The gsdf transcript is expressed mainly in gonadal somatic cells, including Sertoli cell in testis and granulosa cells in ovary; however, these gonadal somatic cells can surround many types of germ cells at different developmental stages depending on the fish species. The function of gsdf is also variable. It is involved in germ cell proliferation, testicular formation, ovarian development and even male sex determination. Here, we summarize the common and diverse expression, regulation and functions of gsdf among different fish species with aspect of evolution.